Application of Generative Networks in Spam Detection in Cybersecurity - Araujo, Milena de Toledo; Costa, Kelton Augusto Pontara da (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.11696, 2025)
This study evaluates the effectiveness of Machine Learning techniques, including classical techniques (Naı̈ve Bayes, Random Forest, KNN, SVM, Logistic Regression) and Deep Learning models (BERT, RoBERTa), in Spam classification. Focusing on data poisoning attacks, it investigates the unethical use of popular generative networks, such as ChatGPT and Gemini, to create malicious messages capable of bypassing intelligent filters. The research also explores the potential of Dual Contrastive Learning to enhance detection capabilities and uses data from YouTube and Twitter.